2016
DOI: 10.7554/elife.13828
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of glucagon signaling prevents or reverses diabetes onset only if residual β-cells persist

Abstract: Glucagon secretion dysregulation in diabetes fosters hyperglycemia. Recent studies report that mice lacking glucagon receptor (Gcgr-/-) do not develop diabetes following streptozotocin (STZ)-mediated ablation of insulin-producing β-cells. Here, we show that diabetes prevention in STZ-treated Gcgr-/- animals requires remnant insulin action originating from spared residual β-cells: these mice indeed became hyperglycemic after insulin receptor blockade. Accordingly, Gcgr-/- mice developed hyperglycemia after indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 56 publications
3
54
1
1
Order By: Relevance
“…Studies in glucagon receptor knockout mice rendered insulin deficient by streptozotocin have firmly demonstrated the metabolic benefits of absence of glucagon action without insulin administration . In addition, we have shown in mice with near absence of insulin receptor signaling that REGN1193 treatment is able to lower glucose to near normal ranges .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Studies in glucagon receptor knockout mice rendered insulin deficient by streptozotocin have firmly demonstrated the metabolic benefits of absence of glucagon action without insulin administration . In addition, we have shown in mice with near absence of insulin receptor signaling that REGN1193 treatment is able to lower glucose to near normal ranges .…”
Section: Discussionmentioning
confidence: 66%
“…Studies in glucagon receptor knockout mice rendered insulin deficient by streptozotocin have firmly demonstrated the metabolic benefits of absence of glucagon action without insulin administration. [18][19][20] In addition, we have shown in mice with near absence of insulin receptor signaling that REGN1193 treatment is able to lower glucose to near normal ranges. 21 Thus, patients with insulin receptor loss of function mutations, manifested as severe insulin resistance and diabetes, ie, Rabson-Mendenhall syndrome and other related diseases, may benefit from anti-glucagon receptor therapy.…”
Section: Discussionmentioning
confidence: 82%
“…In particular, genetic deletion of insulin (49) or the use of diphtheria toxin to induce near complete ablation of β-cells (50) in Gcgr −/− mice nonetheless induced full-blown diabetes. Thus, it has been suggested that a retained low level of insulin, as occurs in the STZ type 1 diabetes model, may be permissive for the blood glucose–lowering effect observed with GcgR antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of complete lack of insulin (e.g. induction of complete loss of β-cells and deletion of the insulin gene), these effects are less prominent, suggesting that some residual β-cell function is critical to maintaining the metabolic phenotype of GCGr knockout mice [10,11]. Notably, deletion of the GCGr gene or blockade of GCGr signalling is accompanied by marked changes in other metabolic regulators, including GLP-1, which complicate elucidation of the mechanisms that contribute to glucose lowering [12].…”
Section: Actions Of Glucagon Signallingmentioning
confidence: 99%